MENGETAHUI PENGARUH KINERJA ISLAM TERHADAP MOTIVASI ISLAM, KOMITMEN ISLAM, DAN PELATIHAN ISLAM PADA KARYAWAN PT. ASURANSI TAKAFUL KELUARGA DI JAKARTA - Yoga Dwi Anugrahadi; Ari Prasetyo (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The bacground of this research is that employees who work at Islamic Financial Institutions (IFIs) get problem both in quantitiy and quality of human resources. This study aims to analyse variables of human resource in Islamic perspective, such as Islamic motivation, Islamic commitment, Islamic training, and Islamic performance. This study used total 64 employees for random sampling observations and using Ordinary Least Square Regression analysis model with SPSS software. Data collection using questionnaire with Linkert scale 1 to 4. This study find partially that Islamic motivation and Islamic commitment are negatively related to Islamic performance, but Islamic training significantly related to Islamic performance. But, this research find that three variables simultanously related together to Islamic performance. Although Islamic training just has influence Islamic performance, therefore Islamic motivation and commitment have positive value in linier regression but in small value.Keywords: Islamic motivation, Islamic commitment, Islamic training, PT. Family Takaful Insurance